PENERAPAN SISTEM INFORMASI AKUNTANSI MANAJEMEN PADA USAHA KECIL MENENGAH DI KOTA PEKANBARU - Aisya Rahma Syakira,; Nurmia Saragih,; Rizky Dwi Anggraini, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
The problems that are often faced by small businesses are related to the problem of management ability or unprofessional management. Management information system is a company's economic tool that supports the running of a business. This research aims to analyze the extent to which the implementation of Management Accounting Information Systems in Micro, Small and Medium Enterprises in Pekanbaru City. The research method used in the preparation of this research is a qualitative method, namely by conducting interviews and descriptive analysis has been carried out. The results of the study indicate that the Information System will provide benefits for producers, suppliers and consumers to manage business processes in MSMEs in Pekanbaru City.